Ginseng and its functional components in non-alcoholic fatty liver disease: therapeutic effects and multi-target pharmacological mechanisms - Xiao, Ping; Ye, Zhaorui; Li, Xiuyan; Feng, Quansheng; Su, Yue (Frontiers in Pharmacology, 2025)
BackgroundNon-alcoholic fatty liver disease (NAFLD) is a common type of chronic liver disease and its incidence is increasing. Its disease progression is closely related to non-alcoholic steatohepatitis and liver fibrosis. Effective treatment is currently lacking. The traditional Chinese medicine ginseng (Panax ginseng) shows unique advantages in NAFLD intervention, but its complex compositional system and molecular mechanism network still need to be systematically analyzed.ObjectiveThis paper systematically integrates evidence from nearly 20 years of research to elucidate the multi-target pharmacological mechanism of ginseng for the treatment of NAFLD.MethodsRelevant information was sourced from Pubmed, Web of science, Embase and CNKI databases. Using BioRender and visio to draw biomedical illustrations.ResultsThe active ingredients of ginseng contain 2 classes of saponins (tetracyclic triterpene saponins, pentacyclic triterpene saponins and other modified types) and non-saponins. Different cultivation methods, processing techniques and extraction sites have expanded the variety of ginseng constituents and demonstrated different pharmacological activities. Studies have shown that ginseng and its functional components have the ability to regulate lipid metabolism disorders, inflammation, oxidative stress, endoplasmic reticulum stress, insulin resistance, disruption of intestinal flora structure, cell death and senescence. Demonstrates the potential of ginseng for the treatment of NAFLD.ConclusionThis study reveals for the first time the integrative mechanism of ginseng in the treatment of NAFLD through the tertiary mode of action of “multi-component multi-target multi-pathway”. The multilevel modulatory ability of ginseng provides a new direction for the development of comprehensive therapeutic strategies for NAFLD.